Pendekatan Strategis Adaptif Berbasis SJSN (BPJS) Dalam Upaya Pengembangan Produk Pensiun Nasional - Yuliyanti M. Manan (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2020)
The Capital Market Industry and Non-Bank Financial Institutions (NBFIs) provide alternative means of investment and financial planning for the public. Funds collected in the capital market and the non-bank financial industry (IKNB) and the movement of funds through the financial markets, including capital markets and non-bank financial institutions, are the main keys to the movement of a country's economy. The ranking of penetration results from the World Bank in 6 Asian countries Indonesia ranks 6th, in order to increase penetration, an adaptive approach based on the National Social Security System (BPJS) is needed, in this case placing the role of the National Health Insurance as a center for developing a national pension program with the strategy of integrating the health benefits of Social Security Health Insurance. and pension services (BPJS-K & P). The purpose of this research is to analyze and study innovation solutions to the development and derivation platform of pension products based on the BPJS program. This study uses a descriptive analytical research design and an actuarial approach to research and develop BPJS-based pension services programs.